About Two Significant Objects. The Cultural Cataloguing of the Kitchen Space (In the Kitchen. Cultural Sketches on Space, 2019)
Author reports on a research exercise, which – trying to maintain the autoethnographic perspective – she made in her own kitchen. She reaches for the tools of sensory ethnography, listens to suggestions of the anthropology of food, to describe herself as a researcher in space, the researcher in relation to things. The topography of the kitchen, the objects it contains, the gestures and practices associated with them become a contribution to cultural comments and analyzes.